Garnet as a monitor for melt–rock interaction: Textural, mineralogical, and compositional evidence of partial melting and melt‐driven metasomatism. (19th February 2021) - Goncalves, Philippe; Raimondo, Tom; Paquette, Jean‐Louis; Santos de Souza de Oliveira, Jailma
Abstract: In this study, we focus on a partially melted garnet‐bearing granulite from the Salvador–Esplanade Belt (Salvador da Bahia, Brazil), and examine the behaviour of major and trace elements during partial melting and melt‐driven metasomatism. Phase equilibria modelling and U–Th–Pb geochronology show that the sample underwent partial melting during the heating segment of the decompression path from ~1.2 GPa and 675–700°C to ~0.8 GPa and 790°C at c . 2.06 Ga. During the final stage of decompression, from 0.8 to ~0.5 GPa, physical segregation of melt resulted in the establishment of chemical potential gradients and mass transfer between the host granulite and the leucosome. Modelling shows that H2 O, CaO, K2 O, and Na2 O diffused from the melt into the host residue, whereas SiO2 was transferred from the host granulite into the adjacent leucosome. Opposed senses of diffusional transfer resulted in the formation of a quartz‐rich anhydrous leucosome and a quartz‐depleted selvedge in the host granulite. Compositional maps show that garnet exhibit contrasting major and trace element distributions depending on their textural position. The largest garnet located in the quartz‐depleted selvedge preserve their original Ca and trace element growth zoning. A transition from bell‐shaped profiles for Y and heavy rare earth elements to bowl‐shaped profiles for light rare earth elements is consistent with a typical Rayleigh fractionation model, fast intergranular element mobility, and rock‐wide equilibrium during prograde partial melting. In contrast, smaller garnet away from the leucosome show prograde growth zoning modified by intragranular diffusion, as evidenced by a network of open channels and healed cracks that act as connecting pathways between the matrix and garnet core. This results in either subtle modification of both major and trace elements adjacent to the inner core inclusions, or a complete re‐equilibration. Recognition that the original Ca growth zoning was later modified by intragranular diffusion implies that misleading thermobarometric results and tectonic interpretations would be obtained if the core composition was used to fingerprint the early garnet nucleation stage. This study demonstrates that at high temperature (>750°C) and in the presence of melt, REE are not less vulnerable to diffusive resetting than divalent cations like Ca 2+ .